2023
DOI: 10.5152/eurasianjmed.2022.22289
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hydatid Cyst in Children and Adults: Diagnosis and Management

Abstract: Hydatid cyst disease induced by Echinococcus granulosus is a parasitic disease known since ancient times. Today, it continues to be seen in many countries and creates serious problems. The lung is the second most frequently affected organ by hydatid cysts after the liver. Lung involvement is more prevalent in children than adults, and the growth of the cyst is faster in children. Hydatid cysts are mostly seen in the right lower lobe of the lung. Common symptoms are chest pain, cough, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…This is due to the high elasticity and compressibility of the lungs in children. [24][25][26] In one retrospective review of pediatric hydatid cysts from our institution, the lung was found to be the most common site of involvement in 76.5% of the children. 27 Pulmonary hydatid cyst was also the most common indication for thoracotomy in a study from Turkey in which it accounted for 35% of the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the high elasticity and compressibility of the lungs in children. [24][25][26] In one retrospective review of pediatric hydatid cysts from our institution, the lung was found to be the most common site of involvement in 76.5% of the children. 27 Pulmonary hydatid cyst was also the most common indication for thoracotomy in a study from Turkey in which it accounted for 35% of the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to the positive E. granulosus -specific IgM and IgG, active tuberculosis, our patients were more likely to have co-infection M. tuberculosis and E. granulosus with lophomonas. The study by Kalani M., et al 2022, mentioned that the prevalence of lophomonas infection was relatively high in patients with suspected tuberculosis due to similar clinical manifestations of this co-infection ( 1 , 2 4 , 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treating pulmonary E. granulosus infection could be pharmacotherapy or surgical intervention, and surgical intervention is the treatment choice. A benzimidazole group (albendazole and mebendazole) could be prescribed for medical treatment [ 4 , 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The choice of surgical approach in HD is influenced by several factors, including cyst size, whether it is intact or complicated, its unilateral or bilateral nature, whether it is solitary or multiple, and the extent of lung parenchyma destruction. Among the various surgical techniques, cystotomy and capitonnage are the most commonly applied methods in clinical practice 23 . In cases where an intact cyst ruptures, prompt surgical intervention becomes imperative to minimize the risk of infection, as the cyst cavity is now in communication with the airway, and the remaining membrane remnants can serve as a nidus for infection.…”
Section: Discussionmentioning
confidence: 99%